Early review of shoulder arthrodesis in brachial plexus injury - Chuan, Wong Chien (2016)
Introduction: Traumatic brachial plexus injury commonly occurs due to road traffic accident, it often leads to long term devastating disability and psychological stress to the affected individual. The injury leads to flail upper limb, impaired sensation and disabling pain. Shoulder arthrodesis is one of the treatment options that improved upper extremities functional outcome. This study intended to evaluate functional outcome of brachial plexus injury after shoulder fusion. Methods: A group of 22 patients with traumatic brachial plexus injury who undergone shoulder fusion from January 2010 until December 2013 were selected. In the end 18 patients were included as study subjects. All selected patients were evaluated for pain score, functional assessment using Quick.DASH questionnaire, and General well-being using SF-36 questionnaire during recent clinic follow up. Results: Shoulder fusion achieved significant reduction in pain among BPI patients . Most of the patient (63.2%) experience moderate difficulty of upper limb function after evaluated with QuickDASH questionnaire. All the patient achieved below average score in Physical Component Summary (PCS) and only 3 (16.7%) patients achieved score average(> 50) in Mental Component Summary (MCS). 16 (88.9%) patients achieved radiological union and only 2 (11.1%) patients had non-union.There were no significant correlation between radiological union and (QuickDASH) functional outcome or (SF36v2) general well-being in this study. Although majority of patient's general health (SF36v2) score below average, they were satisfied and had no regret to undergone shoulder fusion surgery. Conclusions: Shoulder arthrodesis was able to reduce pain in BPI patients. Although majority of patient experience moderate difficulty in upper limb functional score and below average general health score. Most patients were satisfied with the surgery done. Shoulder arthrodesis helps stabilised the shoulder joint which improved control of upper limb function and lead to better quality of life.